Ovarian tumours associated with pregnancy: a five year retrospective study in a tertiary care hospital - N., Sunanda; V., Akhila M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy with ovarian tumors was reviewed over a 5 year period to determine the types of ovarian tumors associated with pregnancy in patients undergoing surgery and also the maternal and fetal outcome. Methods: This retrospective study of 17 cases of ovarian tumors treated surgically during pregnancy and puerperium was carried out at a tertiary hospital between June 2009 and June 2014 to determine the incidence, clinico pathological features and outcome. Results: The overall incidence of ovarian tumor in pregnant woman undergoing surgery was 1 in 1693 (0.025%) deliveries. 52.87% tumors were diagnosed in the first and second trimesters of pregnancy. Ten (58.82%) presented as an emergency at different periods of gestation with torsion being the most common cause of surgery. Serous cyst adenoma (23.52%) and dermoid tumor (17.64%) were the most common types of ovarian tumors found in the study. The incidence of malignant tumors was one (5.88%).Maternal outcome was uneventful in all patients. Abortion rate was 100% in first trimester. Outcome in second trimester is inconclusive as few patients were lost to follow-up. Patients diagnosed in third trimester had an uneventful fetal outcome. Conclusions: Ovarian tumors are encountered with greater frequency, most being benign and self-resolving with malignancy occurring in a small minority of cases. Removal of persisting or enlarging ovarian masses as soon as possible is important to obtain a final histologic diagnosis and rule out malignancy.